Library Services in Spring 2020: Feedback Survey in Tallinn Health Care College, Estonia. Issue 4 (18th February 2022) - Kont, Kate-Riin; Piirsalu, Siret
Abstract: Although patrons have considered the availability and quality of professional literature and library services to be very good, the current survey was conducted under special circumstances. During the Spring of 2020, the library was closed and access to remote services became more relevant. The current study, which was conducted at Tallinn Health Care College in Spring 2020, aims to provide a overview of the user satisfaction level with library services impacted by the lockdown. The questionnaire was conducted online. Libraries and their users suddenly had to confront the fact that access to printed materials was disrupted. We wanted to find out which services were used the most, and which services and resources would be most needed soon. The study revealed several bottlenecks that would not normally have emerged. The library should maintain and strengthen services that satisfy the needs of users, add new services, and work to improve users' awareness of counseling services. College members expect more specific instructions on how to independently find information, how to use databases, and how to find electronic theses. It is customary to have face-to-face consultations in the library, but not yet common to have consultations via online channels. Most respondents are ready to use the book delivery service via parcel machines and are willing to pay a reasonable price for it. The greatest asset of the library is its staff, who has the skills, experience and competencies to offer quick practical solutions to user inquiries both on-site and distance.